1996
DOI: 10.1074/jbc.271.11.6545
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Transit Sequence of Chloroplast Precursor Proteins

Abstract: A protein kinase was located in the cytosol of pea mesophyll cells. The protein kinase phosphorylates, in an ATP-dependent manner, chloroplast-destined precursor proteins but not precursor proteins, which are located to plant mitochondria or plant peroxisomes. The phosphorylation occurs on either serine or threonine residues, depending on the precursor protein used. We demonstrate the specific phosphorylation of the precursor forms of the chloroplast stroma proteins ferredoxin (preFd), small subunit of ribulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(166 citation statements)
references
References 58 publications
(67 reference statements)
6
157
1
2
Order By: Relevance
“…2 The amino acid sequence around Ser-113 does not resemble any other canonical phosphorylation motif found in the PROSITE data base. This indicates that the Toc34 kinase may not belong to a conventional protein kinase class.…”
Section: Preprotein Receptor Toc159 Is a Phosphoprotein-certainmentioning
confidence: 92%
See 1 more Smart Citation
“…2 The amino acid sequence around Ser-113 does not resemble any other canonical phosphorylation motif found in the PROSITE data base. This indicates that the Toc34 kinase may not belong to a conventional protein kinase class.…”
Section: Preprotein Receptor Toc159 Is a Phosphoprotein-certainmentioning
confidence: 92%
“…In recent years, evidence has accumulated that protein phosphorylation and protein kinases play an important role in regulation and fine-tuning of protein translocation into various subcellular compartments. Upon translation in the cytosol, chloroplast, but not mitochondrial or peroxisomal, preprotein targeting sequences are phosphorylated by a specific protein kinase (2). Phosphorylated preproteins engage an oligomeric guidance complex consisting of a 14-3-3 protein dimer and a cytosolic Hsp70 (3).…”
Section: From the ‡Botanisches Institut Der Christian-albrechts-univementioning
confidence: 99%
“…Instead, it has been proposed that cytosolic factors may target precursors to the chloroplast surface (Schnell and Blobel, 1993). Indeed, a cytosolic member of the 14-3-3 family of proteins has been identified that binds to phosphorylated transit sequences (Waegemann and Soll, 1996) and thus forms a guidance complex to deliver precursor proteins to the Toc-complex (May and Soll, 2000). Recently, we have discovered that atToc159 also exists in an abundant soluble form, partitioning between the outer chloroplast membrane and the cytosol (Hiltbrunner et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…Four distinct plant transit peptides features are; (1) phosphorylation and dephosphorylation of specific motifs in transit peptides prior to import (this may explain in part the need for hydroxylated residues that can be phosphorylated) (Waegemann and Soll, 1996;Jarvis and Soll, 2001), (2) the presence of Hsp70 recognition domains that mediate binding of these and other cytosolic proteins on route to the chloroplasts (Ivey et al, 2000), (3) specific interactions of transit peptides with chloroplast-specific membrane lipids, and (4) one or more transit peptide domains forming α-helical structures upon contact with the chloroplast membrane lipids. It has recently been noted that Plasmodium transit peptides also typically contain predicted Hsp70 binding domains, and that transit peptide function is sensitive to alterations at these sites (Foth et al, 2003).…”
Section: Apicoplast Transit Peptidesmentioning
confidence: 99%